2020
DOI: 10.1111/1365-2745.13562
|View full text |Cite
|
Sign up to set email alerts
|

Competition for pollination and isolation from mates differentially impact four stages of pollination in a model grassland perennial

Abstract: 1. Species that persist in small populations isolated by habitat destruction may experience reproductive failure. Self-incompatible plants face dual threats of matelimitation and competition with co-flowering plants for pollination services. Such competition may lower pollinator visitation, increase heterospecific pollen transfer and reduce the likelihood that a visit results in successful pollination. 2. To understand how isolation from mates and competition with co-flowering species contribute to reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 58 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…speciosa , which had a neutral relationship between flowering synchrony and seed set. Competition for pollination in these populations may also influence the relationship between individual within‐year flowering synchrony and reproductive success (Richardson et al ., 2021). Seed set probably reflects pollination rather than resource availability in L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…speciosa , which had a neutral relationship between flowering synchrony and seed set. Competition for pollination in these populations may also influence the relationship between individual within‐year flowering synchrony and reproductive success (Richardson et al ., 2021). Seed set probably reflects pollination rather than resource availability in L .…”
Section: Discussionmentioning
confidence: 99%
“…Second, small or isolated populations, which are common in fragmented habitat, are more likely to experience mate‐finding Allee effects (Davis et al ., 2004; Wagenius et al ., 2007). Third, when individuals of a given species flower infrequently, such that only a fraction of adult plants flower in any given year, they are vulnerable to reduced reproductive success (Waananen et al ., 2018), despite pollinator visitation (Wagenius & Lyon, 2010; Richardson et al ., 2021). Many prairie perennials flower infrequently, are self‐incompatible, and persist in fragmented habitat, making them vulnerable to mate‐finding Allee effects.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of co‐flowering species has been found to decrease the pollination success of focal species in several systems (Caruso 1999; Landry 2013; Richardson et al. 2021), but some studies have shown the opposite trend (i.e., facilitation) in other species pairs (Moeller 2004; Tur et al. 2016; Bergamo et al.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that despite extensive pollinator sharing, the presence of G. densiflora does not increase competition for pollinator visits in G. conopsea (and vice versa). The presence of co-flowering species has been found to decrease the pollination success of focal species in several systems (Caruso 1999;Landry 2013;Richardson et al 2021), but some studies have shown the opposite trend (i.e., facilitation) in other species pairs (Moeller 2004;Tur et al 2016;Bergamo et al 2020). Moreover, the sign of pollinator-mediated interactions between plant species may be context dependent.…”
Section: No Cost Of Pollinator Sharingmentioning
confidence: 99%
“…Over 70% of plants depend to some degree on animal pollinators to successfully reproduce (Ollerton et al, 2011). Among the diversity of pollinators, taxa vary in their contributions to pollination in multiple intricate dimensions, some quantitative (e.g., numbers of visits, numbers of pollen grains transferred: Herrera, 1987; King et al, 2013), others qualitative (e.g., proportion selfed vs. outcrossed pollen, diversity of mates, spatial distances of mating: Valverde et al, 2019; Richardson et al, 2021). At its core, the functional contributions of different pollinator taxa can be measured by the quantity (frequency) and quality (effectiveness) of visits to plant reproductive success (Inouye et al, 1994; King et al, 2013).…”
mentioning
confidence: 99%